Community media research - Jankowski, Nicholas W. (Javnost (Ljubljana), 2003)
This article provides a panoramic sketch of the characteristics of community media and focuses on three forms: community television, community radio and community networks. The author contends, after a review of research conducted around these media, that much of this work has contributed little to the development of theoretical perspectives and theoretical model building suitable for guiding further empirical investigations. An illustration, taken from one theoretical perspective, is provided of the kind of model building that can be achieved. In conclusion, community media researchers are encouraged to take up the challenge associated with the general mandate for social scientists to contribute to theory, in this case through construction of theoretically-grounded models for understanding the place of community media in society.
Keywords: lokalne skupnosti; manjšine; interesi; množične komunikacije; množični mediji; mass media; vplivi